The effect of GP telephone triage on numbers seeking same-day appointments. - Jiwa, Moyez; Mathers, N.; Campbell, M. (Royal College of General Practitioners, 2004)
Telephone consultations with general practitioners (GPs) have not been shown to be an effective way to reduce the demandfor face-to face appointments during the surgery hours. This study aims to determine if GP telephone triage can effectively reduce the demandforface-to -face consultations for patients seeking same-day appointments in general practice. We report an interrupted time series, twoyears before and one year after introduction of GP-led telephone triage. Demand for face-to face appointments with a GPwas reduced by 39% (95% CI = 29 to 51%, P < 0.001). more than 92% of the telephone calls lasted less thanfive minutes. The telephone bill increased by 26%. For a substantial proportion of patients seeking same-day appointments telephone consultations were an acceptable alternative service.